The X-ray emissivity of low-density stellar populations. Issue 4 (24th January 2020) - Heinke, C O; Ivanov, M G; Koch, E W; Andrews, R; Chomiuk, L; Cohn, H N; Crothers, S; de Boer, T; Ivanova, N; Kong, A K H; Leigh, N W C; Lugger, P M; et al.
ABSTRACT: The dynamical production of low-mass X-ray binaries and brighter cataclysmic variables (CVs) in dense globular clusters is well-established. We investigate how the X-ray emissivity of fainter X-ray binaries (principally CVs and coronally active binaries) varies between different environments. We compile calculations (largely from the literature) of the X-ray emissivity of old stellar populations, including open and globular clusters and several galaxies. We investigate three literature claims of unusual X-ray sources in low-density stellar populations. We show that a suggested quiescent neutron star in the open cluster NGC 6819 is a foreground M dwarf. We show that the suggested diffuse X-ray emission from an old nova shell in the globular cluster NGC 6366 is actually a background galaxy cluster. And we show that a suggested population of quiescent X-ray binaries in the Sculptor Dwarf Galaxy is mostly (perhaps entirely) background galaxies. We find that above densities of 10 4 M⊙ pc −3, the X-ray emissivity of globular clusters increases, due to dynamical production of X-ray emitting systems. Below this density, globular clusters have lower X-ray emissivity than the other populations, and we do not see a strong dependence of X-ray emissivity due to density effects. We find significant correlations between X-ray emissivity and binary fraction, metallicity, and density. Sampling these fits via bootstrap techniques gives less significant correlations, but confirms the effect of metallicity on low-density populations, and that of density on the full globular cluster sample.